Using Translation to Teach Native and Non-native Varieties of International English - Guerra, Luis (2015)
The term ‘New Englishes’ attempts to cover the large number of varieties of English, far from uniform among themselves in their features and use and different from the historically and culturally established British and American standards. Over the past years, these New Englishes have been more acknowledged in the foreign language class. Linguists have called attention to the importance of increasing the learner’s linguistic awareness by covering topics of “linguistic variation and varieties of many types: national, regional, social, functional, international” (Gnutzmann 167). This paper aims at discussing the advantages and possibilities of teaching native and non-native English varieties in the foreign language class. It presents some data included in a Foreign Language and Translation course which attempted to integrate linguistics and translation by analysing the features of African American Vernacular English, Singapore English, Indian English and Australian English in terms of their phonological, morphological, lexical and syntactic levels.